Maia: an Open Collaborative Platform for Text Annotation, E-Lexicography, and Lexical Linking - Giovannetti, Emiliano; Albanesi, Davide; Bellandi, Andrea; Marchi, Simone; Papini, Mafalda; Sciolette, Flavia (Umanistica Digitale, 2024)
Although open tools for manual text annotation and the creation of lexical resources have been available for some years, there is currently no integrated tool that allows, within the same environment, annotating a text corpus, building a computational lexicon, and linking linguistic annotations to lexical elements. For this reason, we have developed Maia, an open and collaborative web tool based on semantic web and linked open data technologies for text annotation, e-lexicography, and lexical linking, primarily designed and developed for use by digital humanists. This article presents the first version of Maia, describing its functionality, and outlining its software architecture and development prospects.